PEMBINAAN PERENCANAAN PEMASARAN BAGI PEDAGANG TAS DI KOTA BATAM - Raymond; Dian Lestari Siregar; Mohamad Gita Indrawan (Jurnal Pendekar Nusantara, 2024)
Many MSMEs fail in the initial operational process, one of the reasons for the failure of these MSMEs is a lack of analysis of the perencanaan pemasaranning of the business being carried out. The object that will be fostered in this service is the Indona shop, which is an MSME that operates in the sale of bags. This drug store is located in the Hawai Garden Complex No. 71 Batam center, currently the Indona shop is owned by Mrs. Indona Damayanti. Indona shop sells various bags for both women and children. For this reason, community service is coaching in understanding and making business perencanaan pemasarans, the method used in community service this time is first, the Lecturer Team gives lectures and presentations on business perencanaan pemasaranning theory, second, participants will be given coaching in making business perencanaan pemasarans, third, participants will be given the opportunity to discuss the problems faced in making business perencanaan pemasarans. It is hoped that this community service program can make a contribution in the form of firstly participants being motivated to make business perencanaan pemasarans, secondly participants being able to be skilled in making business perencanaan pemasarans